The Influence Of Tea Types In Making Kombucha On The Taste And Preference Of Hoteliers In Batam - Rizhon Rizhon; Siska Amelia Maldin (Jurnal Indonesia Sosial Teknologi, 2023)
Kombucha is a popular drink with its benefits for human health. This tea-based drink is very famous in the world of tourism for its sour and refreshing taste. Kombucha is generally made using green tea or black tea. However, many types of tea can be used, such as white tea, oolong tea, and so on. Usually, kombucha is made using tea, sugar, and water, then given bacteria and fungi to ferment for around 7 – 15 days. This research aims to see how the use of tea as a basic ingredient affects the taste and preferences of hoteliers in Batam, where 15 panelists carried out organoleptic tests on 8 samples of kombucha that have been prepared, where the only differentiating variable is the type of tea used, the results found that kombucha that is made from green tea is most liked by the panelists, meanwhile, the kombucha that is made from black tea is least liked.